Assessing the relationship between community dispersion and disturbance in a soft‐sediment ecosystem. (4th September 2018) - Gerwing, Travis G.; Allen Gerwing, Alyssa M.; Macdonald, Tara; Cox, Kieran; Juanes, Francis; Dudas, Sarah E.
Abstract: Disturbed ecosystems often exhibit increased community heterogeneity when compared to nondisturbed systems. One way to measure community heterogeneity is statistical dispersion, a measure of how variable individual samples are from the multivariate average of the community condition (species presence/absence and density). In more specific manner, dispersion measures the distance between an individual data point and the centroid, the multivariate average of all data points. Statistical dispersion may be an important parameter to include in environmental assessments, or in studies that attempt to understand the role of disturbances in structuring biological systems. However, disturbances have been observed to increase, decrease, or not impact community dispersion (or community heterogeneity). Therefore, the usefulness of dispersion in studying or identifying disturbances is unclear. We tested if a mechanical disturbance increased community dispersion using the infaunal community of the intertidal mudflats along the north coast of British Columbia, Canada. We observed no statistically significant increase in community dispersion with varying frequency and intensity of a mechanical disturbance. This is likely a result of disturbed and nondisturbed treatments being dominated by the same six taxa, thus minimizing dispersion. Therefore, in ecosystems where differences in community successional stages are subtle (a result of changes in relative abundance rather than species replacement), community dispersion may not be an informative parameter when investigating disturbance. Despite this, we suggest that dispersion can be a useful variable to include in studies attempting to understand or identify disturbances; however, dispersion should only be one parameter amongst many used to understand or identify disturbances.